Riscos ocupacionais e acidentes de trabalho em um serviço de atendimento móvel de urgência do Rio Grande do Norte - Costa, Isabel Karolyne Fernandes (2011)
Exploratory, descriptive and quantitative study with prospective data, performed in the Mobile Emergency Care Service in the metropolitan region of Natal/RN, in order to identify the knowledge of the multidisciplinary team about the rules of standard precautions and worker safety, to identify occupational hazards peculiar to the activities of this service; characterize work-related accidents (WRA) and know the procedures adopted after each WRA. The population consisted of 162 professionals and data were collected between the months of November and December 2010. As for personal and professional characteristics, of the 162 professional, 12,96% were physicians; 6,79%, nurses; 33,95%, nursing technicians, 46,29%, conductors; 74,70% were male; 43,21% were between 31 and 40 years old; 69,33% lived in Natal/RN, 50,00% had completed high school; 58,64% were married; 69,75% had children, 46,91% were between 1 and 4 years of training; 61,73% had improvement courses; 59,25% had 3 to 4 years of service; 54,32%, with 1-4 years experience in emergency; 44,44% received 1-2 minimum wages; 78,40% received insalubrity premium; 67,28% worked in Basic Support Unit (BSU); 83,95% had journey on SAMU Metropolitano of 31-40 hours per week; 52,47% had other employments. As for knowledge of rules of standard precautions, safety and occupational hazards, 99,38% knew what it was WRA; 62,96% gave incomplete answers; 74,07% knew the rules of prevent WRA; 46,67% acquired this knowledge in lectures; 53,09% knew Personal Protective Equipment (PPE); 71,60% gave incorrect answers about the importance of standard precautions; 45,06% never received an educational intervention on this issue; 89,51% said that educational interventions in the prevention of WRA are very important; 90,12% pointed out this as a very important issue in the workplace; 27,00% suggested guidance on the topic in the workplace; regarding the physical hazards, 34,57% considered noise as the most important; about chemical hazards, 78,40% chose the gases and smoke; for biological hazards, 48,77% reported contact with the blood; for mechanical hazards, 80,86% said that were transport accidents; about ergonomic risks, 40,12% say it is the tension/stress in the care of critically ill, psychiatric and aggressive patients; and there was an average of 4,5 to the feeling of safety in the workplace. Regarding the data on the WRAs occurred, 31,48% experienced at least one accident event; 72,55% did not notify it; 60,98% answered that there was no routine for notification; 56,86% were performing patient transportation; 49,02% were hurt in the Basic Support Unit/Rescue Unit (BSU/RH); 60,78% occurred during the day; 96,08% of professionals were in normal work schedule (24 hours on duty); 31,37% had contusion; 58.82% had damage to members/pelvic girdle; 43,14% had traffic accidents. About the evolution of the WRA, 62,75% did not have to take time away from work; 76,47% had no sequelae; 88,24% did not require rehabilitation; no professional had a change of occupation. And by means of univariate logistic regression, showed that the nurses and male sex were risk factors for the occurrence of WRA. We conclude that there were gaps in the knowledge of staff regarding WRA, emphasizing the need for continuing education in biosafety in the service.